The sigma 54 genes rpoN1 and rpoN2 of Xanthomonas citri subsp. citri play different roles in virulence, nutrient utilization and cell motility - Gibson Kamau Gicharu; Dong-ling SUN; Xun HU; Xiao-jing FAN; Tao ZHUO; Chuan-wan WU; Hua-song ZOU (Journal of Integrative Agriculture, 2016)
The sigma factor 54 (σ54) controls the expression of many genes in response to nutritional and environmental conditions. There are two σ54 genes, rpoN1 (XAC1969) and rpoN2 (XAC2972), in Xanthomonas citri subsp. citri. To investigate their functions, the deletion mutants ΔrpoN1, ΔrpoN2 and ΔrpoN1N2 were constructed in this study. All the mutants delayed canker development in low concentration inoculation in citrus plants. The bacterial growth of mutants was retarded in the medium supplemented with nitrogen and carbon resources. Under either condition, the influence degree caused by deletion of rpoN2 was larger than the deletion of rpoN1. Remarkably, the mutant ΔrpoN1 showed a reduction in cell motility, while the mutant ΔrpoN2 increased cell motility. Our data suggested that the rpoN1 and rpoN2 play diverse roles in X. citri subsp. citri.